2014
DOI: 10.1155/2014/297203
|View full text |Cite
|
Sign up to set email alerts
|

Noninterventional Open-Label Trial Investigating the Efficacy and Safety of Ectoine Containing Nasal Spray in Comparison with Beclomethasone Nasal Spray in Patients with Allergic Rhinitis

Abstract: Objectives. The current study aimed to compare the efficacy and safety of a classical anti-inflammatory beclomethasone nasal spray in comparison to a physic-chemical stabilizing ectoine containing nasal spray in the treatment of allergic rhinitis. Design and Methods. This was a noninterventional, open-label, observational trial investigating the effects of beclomethasone or ectoine nasal spray on nasal symptoms and quality of life. Over a period of 14 days, patients were asked to daily document their symptoms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…These results are in line with those demonstrated in this NIS. Ectoine-containing nasal spray, however, was shown to be inferior to BNS [28].…”
Section: Discussionmentioning
confidence: 86%
“…These results are in line with those demonstrated in this NIS. Ectoine-containing nasal spray, however, was shown to be inferior to BNS [28].…”
Section: Discussionmentioning
confidence: 86%
“…Some studies showed that products containing ectoine may be a better alternative to other products, as they reduce ocular and nasal symptoms with no side effects (40)(41)(42). Promising effects such as reduction of nasal airway obstruction and crust formation were also observed in patients with rhinitis sicca anterior treated with nasal spray containing ectoine alone or in combination with dexpanthenol (43). Moreover, a recent study has shown that a mouth and throat spray containing ectoine can be very effective in the treatment of acute pharyngitis and laryngitis (44).…”
Section: Alleviation Of Inflammatory Reactionmentioning
confidence: 99%
“…Ektoina (kwas 1,4,5,6-tetrahydro-2-metylo-4-pyrimidynokarboksylowy) to cząsteczka naturalnie produkowana przez ekstromofile, bakterie żyjące w trudnych warunkach środowiska. Tworzy ona naturalną barierę ochronną przed oddziaływaniem czynników szkodliwych, takich jak wysoka temperatura, promieniowanie ultrafioletowe czy nadmierna suchość [8,9]. Ekstromofile nabywają odporność poprzez zmianę składu lipidów w błonach komórkowy i regulację wewnątrzkomórkowego stężenia substancji rozpuszczonych o niskiej masie cząsteczkowej, takich jak kompatybilny rozpuszczony roztwór ektoiny.…”
Section: Ektoinaunclassified
“…Ekstromofile nabywają odporność poprzez zmianę składu lipidów w błonach komórkowy i regulację wewnątrzkomórkowego stężenia substancji rozpuszczonych o niskiej masie cząsteczkowej, takich jak kompatybilny rozpuszczony roztwór ektoiny. W badaniach wykazano, że ektoina zapewnia ochronę komórek nabłonkowych, stabilizuje błony komórkowe, nawilża powierzchnię oraz zmniejsza stan zapalny [8][9][10][11][12][13].…”
Section: Ektoinaunclassified
See 1 more Smart Citation